2008
DOI: 10.1097/icl.0b013e31815788ea
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Contact Lens Materials and Contact Lens–Wearing Periods on Conjunctival Cytology in Asymptomatic Contact Lens Wearers

Abstract: Conjunctival cytologic changes occurred in asymptomatic contact lens wearers and were related to the duration of lens wear. For this reason, asymptomatic contact lens wearers may be followed up because of conjunctival cytologic changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 12 publications
0
9
0
2
Order By: Relevance
“…22,23 The presence of vital dye staining of the CEF after long periods of CW could indicate insufficient mucin protection. Because mucin-producing goblet cells are found to be present in the CEF, and goblet cell density has been shown to decrease with prolonged contact lens wear, 24 there is concern that the normal balance of tear film components could be locally disrupted, eventually leading to tear film instability and associated dry eye symptoms. 25,26 In larger CEF, fluorescein is seen to pool at the margin of the flap.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 The presence of vital dye staining of the CEF after long periods of CW could indicate insufficient mucin protection. Because mucin-producing goblet cells are found to be present in the CEF, and goblet cell density has been shown to decrease with prolonged contact lens wear, 24 there is concern that the normal balance of tear film components could be locally disrupted, eventually leading to tear film instability and associated dry eye symptoms. 25,26 In larger CEF, fluorescein is seen to pool at the margin of the flap.…”
Section: Discussionmentioning
confidence: 99%
“…16 40 gözde hidroksimetilmetakrilat, 70 gözde polymacon olmak üzere iki farklı geleneksel hidrojel KL ile 40 gözde sert gaz geçirgen olmak üzere üç farklı kontakt lens materyalinin konjonktiva yüzeyinde yaptığı değişimleri impresyon sitolojisi ile karşılaştırmıştır. Tüm lens materyallerinde konjonktivada epitel hücre değişiklikleri ve goblet hücre dansitesinde azalma saptanmış, ancak bu değişiklikler her üç grup kontakt lens arasında istatistiksel olarak anlamlı farklı bulunmamıştır.…”
Section: Discussionunclassified
“…Bazı çalışmalar lens kullanım süresi ile konjonktiva yüzeyi sitolojik değişiklikleri arasında bir ilişki saptamamışken 4,18,15 , bazı çalışmalar kullanım süresi ile sitolojik değişiklikler arasında bir ilişki saptamıştır. 8,16,19,20 Simone ve ark. 8 sert gaz geçirgen ve yumuşak kontakt lens kullanan 50 hastada yaptığı bir çalışmada 3-6. ayda dahi her iki kontakt lens grubunda da konjonktiva yüzeyi sitolojik değişikliklerinin bazale oranla belirgin farklılık gösterdiğini, sitolojik değişikliklerin lens kullanım süresi ile artış gösterdiğini belirtmişlerdir.…”
Section: Discussionunclassified
“…20 Lastly, a set of contact lens wearers, assessed by CIC after only a short period of contact lens wear might include a mixture of normal (grade 0) and low squamous metaplasia grades (i.e., mostly grade 1) thus yielding a low mean grade with a proportionately higher SD (and thus higher COV). 29 Overall, an analysis of the COV (i.e., SD/mean grade 3 100%) across all 16 studies (data not shown) or just the 13 studies with robust details of duration of contact lens wear (Fig. 3) reveals a notable trend.…”
Section: Development Of Conjunctival Squamous Metaplasia In Contact Lmentioning
confidence: 90%
“…36,38,39 Across the 16 suitable studies for analysis, the reported or estimated squamous metaplasia grades covered the full range from 0 to 3, or equivalents of this range. For any particular study, that also included details of contact lens wearing period, evaluation of the investigators' data revealed mean values between 0.87 and 2.25 for the squamous metaplasia grade [14][15][16][17][18][19][20][21][22][23][24][25][26]28,29 ; one study indicated a mean squamous metaplasia grade of just 0.89 but no details of the duration of contact lens wear. 27 As noted earlier, two studies provide only a grouping of contact lens wear into periods of less than 1 year or greater than 1 year, 16,26 so there is a degree of uncertainty as to the extent of contact lens wear, and such information is also not amenable to averaging.…”
Section: Development Of Conjunctival Squamous Metaplasia In Contact Lmentioning
confidence: 99%